BMAL1/FOXA2-induced rhythmic fluctuations in IL-6 contribute to nocturnal asthma attacks - Tang, Lingling; Liu, Li; Sun, Xianhong; Hu, Po; Zhang, Hui; Wang, Bohan; Zhang, Xiaona; Jiang, Jinjin; Zhao, Xia; Shi, Xiaolu (Frontiers in Immunology, 2022)
The circadian clock is closely associated with inflammatory reactions. Increased inflammatory cytokine levels have been detected in the airways of nocturnal asthma. However, the mechanisms that contribute to the nocturnal increase in inflammatory responses and the relationship with circadian clock remain unknown. Methods Inflammatory cytokine levels were measured in asthma patients with and without nocturnal symptoms. Allergic airway disease was induced in mice by ovalbumin (OVA), and different periods of light/dark cycles were used to induce circadian rhythm disorders. Serum shock was used to stimulate the rhythmic expression in human bronchial epidermal cells (16HBE). The expression and oscillation of circadian clock genes and inflammatory cytokines in 16HBE cells subjected to brain and muscle ARNT-like protein-1 (BMAL1) and Forkhead Box A2 (FOXA2) knockdown and treatment with a FOXA2 overexpression plasmid were assessed. Results Serum IL-6 was found to be significantly higher in asthmatic patients with nocturnal symptoms than those without nocturnal symptoms. The OVA-induced asthma model with a circadian rhythm disorder and 16HBE cells treated with serum shock showed an increase in IL-6 levels and a negative correlation with BMAL1 and FOXA2. The knockdown of BMAL1 resulted in a lower correlation between IL-6 and other rhythm clock genes. Furthermore, knockdown of the BMAL1 and FOXA2 in 16HBE cells reduced the expression and rhythmic fluctuations of IL-6. Conclusions Our findings suggest that there are increased IL-6 levels in nocturnal asthma resulting from inhibition of the BMAL1/FOXA2 signalling pathway in airway epithelial cells.